Sulfate source apportionment in the Ny-Ålesund (Svalbard Islands) Arctic aerosol - Udisti, R; Bazzano, A; Becagli, S; Caiazzo, L; Cappelletti, D; Frosini, D; Giardi, F; Grotti, M; Lupi, A; Malandrino, M; Mazzola, M; Moroni, B; et al. (Rendiconti Lincei, 2016)
Daily PM10 aerosol samples were collected at the Gruvebadet observatory, Ny-Ålesund (Svalbard Islands), during the spring-summer 2014 Italian Arctic Campaign. A total of 136 samples were analysed for ion (inorganic anions and cations, selected organic anions) composition aiming to evaluate the seasonal pattern of sulfate, as a key component of the Arctic haze. Ionic balances indicated a strong sulfate seasonality with mean spring concentration about 1.5 times higher than that measured in summer. The spring and summer aerosol was almost neutral, indicating that ammonia was the major neutralizing agent for atmospheric acidic species. The linear regression between sulfate from potential acidic sources (non-sea salt sulfate and non-crustal sulfate) and ammonium indicated that the mean sulfate/ammonium ratio was intermediate between semi-(NH4HSO4) and complete ((NH4)2SO4) neutralization. Using sea-salt sodium as sea-spray marker, non-sea-salt calcium as crustal marker and methanesulfonic acid as biogenic marker, a detailed source apportionment for sulfate was carried out. The anthropogenic input (calculated as the differences between total sulfate and the sum of sea-salt, crustal and biogenic contributes) was found to be the most relevant contribution to the sulfate budget in the Ny-Ålesund aerosol in summer and, especially, in spring. In this last season, crustal, sea-salt, biogenic and anthropogenic sources accounted for 3.3, 12.0, 11.5 and 74.8 %, respectively.